Enhancement of Keratin Degrading Ability of Bacillus sp. Through Optimization of Submerged Fermentation: Enhancement of Keratin Degrading Ability of Bacillus sp. - Fatima Jamil; Yesra Arshad; Hamid Mukhtar (Biological Sciences - PJSIR, 2023)
Keratinases have a broad range of bio-technological, pharmaceutical, industrial, agricultural and eco-friendly waste management applications owing to their ability of degrading insoluble keratin waste. The present study aims to enhance keratinase production by optimizing some production parameters during sub-merged fermentation, using Bacillus sp. In this study, total 26 bacterial strains were isolated from four different localities in Lahore i.e. Tollinton market, chicken shops in Faisal town, Johar town and Walton cantt and screened for proteolytic activity on skim milk agar. After screening for keratinolytic activity using chicken feathers as a substrate, five strains were selected. These selected strains were identified as Bacillus sp. based on their micro-morphology and biochemical tests. Out of all the selected FK-22 exhibited the maximum keratinase activity (6.86 U/mL) which was further optimized for enhanced keratinase production. The highest yield of 19.04 U/mL was obtained using medium 1 at pH 8 after 7 days of incubation at 40 °C.